2014
DOI: 10.1097/dcr.0000000000000038
|View full text |Cite
|
Sign up to set email alerts
|

Complication Rates of Ostomy Surgery Are High and Vary Significantly Between Hospitals

Abstract: Structured Abstract Background Ostomy surgery is common and has traditionally been associated with high rates of morbidity and mortality, suggesting an important target for quality improvement. Objective To evaluate the variation in outcomes after ostomy creation surgery within Michigan in order to identify targets for quality improvement. Design Retrospective cohort study. Setting The 34-hospital Michigan Surgical Quality Collaborative (MSQC). Patients Patients undergoing ostomy creation surgery betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
63
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 20 publications
5
63
0
2
Order By: Relevance
“…These findings are comparable with other studies investigating the morbidity and mortality rates of diverting stomas. [16][17][18][19][20][21] Additionally, several risk factors leading to a permanent stoma in initially defunctioned patients after rectal resection must be considered. 35,36 In our series, only 2 patients were not reversed at the time of analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are comparable with other studies investigating the morbidity and mortality rates of diverting stomas. [16][17][18][19][20][21] Additionally, several risk factors leading to a permanent stoma in initially defunctioned patients after rectal resection must be considered. 35,36 In our series, only 2 patients were not reversed at the time of analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, stoma reversal also implies a secondary hospital stay and several temporary stomas become permanent. 20,21 Another technique reported to reduce possibly leakage rates is to perform a colonic J-pouch for reconstruction in low anastomoses. 12,13 A pouch may improve leakage rates most likely owing to an improved blood supply to the apex of the pouch 22 and may help to avoid a protective stoma.…”
mentioning
confidence: 99%
“…one recent population-based study based on national surgical Quality improvement Program data showed a 37% unadjusted complication rate for elective cases involving an ostomy, and 55% for emergency operations. 2 furthermore, risk-adjusted morbidity rates varied significantly among hospitals, indicating the potential to improve outcomes. 2 however, the true morbidity of ostomy surgery includes significant negative effects on quality of life, plus longer-term morbidity related to ostomy care.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…2 furthermore, risk-adjusted morbidity rates varied significantly among hospitals, indicating the potential to improve outcomes. 2 however, the true morbidity of ostomy surgery includes significant negative effects on quality of life, plus longer-term morbidity related to ostomy care. [3][4][5][6][7][8][9][10] up to half of ostomies are "problematic," presenting management problems including skin irritation and pouching difficulties that require prolonged medical care and result in increased health care costs (prolonged length of stay and/ or increased need for outpatient care).…”
Section: Statement Of the Problemmentioning
confidence: 99%
“… 6 A majority of these individuals experience life adjustment difficulties 7 and postoperative complications. 8 Such postoperative complications often lead to unexpected hospital readmissions 9 and may also result in emergency room (ER) visits. According to US hospital readmission statistics from the Healthcare Cost and Utilization Project (HCUP), 10 ileostomies and other fecal ostomies had the second highest 30-day readmission rates.…”
Section: Introductionmentioning
confidence: 99%